LEVEL OF WILLING FOR RELOCATION OF FARMERS IN PUSONG RESERVOIR, BANDA SAKTI SUB-DISTRICT LHOKSEUMAWE CITY - Intan Maulina, Cut; Nugroho, Agus; Mustafa, Mustafa (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2023)
The decline in water quality in the Pusong reservoir, Banda Sakti sub-district, Lhokseumawe city, has made the Lhokseumawe City Government try to improve the reservoir's water quality by planning a policy for relocating fish cage farmers from the Pusong reservoir to another place. This study aims to identify the characteristics of the Pusong reservoir farmers, and identify the level of willingness to relocate the Pusong reservoir farmers. This research uses a descriptive method. The subjects in this study were the farmers of the Pusong reservoir, which consisted of 53 farmers from the village of Pusong Lama and 21 farmers from the village of Keude Aceh. The results of the study showed that there were differences in characteristics between the farmers of Pusong Lama Village and Keude Aceh Village, namely in the classification of the age of the farmers and the length of time they had been pondering. Farmers in Pusong Lama village are dominated by farmers aged 40 to 49 years, while farmers in Keude Aceh village are dominated by farmers aged 30 to 39 years. The farmers in Pusong Lama Village are dominated by farmers who have ponded in the Pusong Reservoir for 11 to 15 years, while the farmers in Keude Aceh are dominated by farmers who have ponded for 1 to 10 years. The level of willingness to relocate farmers in the old Pusong village shows that 49% of farmers stated that they strongly disagree and 35% of farmers stated that they did not agree with the policy planning for the relocation of the Pusong reservoir. The level of willingness to relocate farmers in the old Pusong village showed that 56% of the farmers stated that they strongly disagreed and 11% of the farmers stated that they did not agree with the policy planning for the relocation of the Pusong reservoir. while the farmers in the village of Keude aceh are dominated by farmers aged 30 to 39 years. The farmers in Pusong Lama Village are dominated by farmers who have ponded in the Pusong Reservoir for 11 to 15 years, while the farmers in Keude Aceh are dominated by farmers who have ponded for 1 to 10 years